(untitled) (Al-Qamar, 2025)
This study offers a critical evaluation of Peter Cottrell’s Muhammad: The Man Who Transformed Arabia. While introduced as a historical biography, the work reflects a pronounced orientalist bias, largely echoing the framework of W. Montgomery Watt. Cottrell systematically reduces the spiritual, moral, and revelatory aspects of the Prophet Muhammad’s (PBUH) mission to purely political and socio-cultural explanations. His narrative distorts the Prophet’s marriages, detaching them from their ethical wisdom and social necessity, and interprets the military campaigns as calculated political maneuvers rather than divinely guided struggles for justice and peace. Moreover, the book casts suspicion on the authenticity of the Qur’an and Hadith, and even questions the Prophet’s noble lineage (Nasb-e-Mutahharra), overlooking the rigor of traditional Islamic scholarship. The analysis reveals methodological weaknesses, selective use of sources, and continuity with earlier orientalist traditions. The study concludes that although the book is accessible in style, it fails as an impartial or comprehensive account and instead perpetuates misconceptions, reinforcing a reductionist Western paradigm in Seerah studies.